2017
DOI: 10.1111/hsc.12477
|View full text |Cite
|
Sign up to set email alerts
|

Volunteer peer support and befriending for carers of people living with dementia: An exploration of volunteers’ experiences

Abstract: With ageing populations and greater reliance on the voluntary sector, the number of volunteer-led peer support and befriending services for carers of people with dementia in England is set to increase. However, little is known about the experiences of the volunteers who deliver these interventions, many of whom are former carers. Using in-depth semi-structured interviews with 10 volunteer peer supporters and befrienders, this exploratory study investigated volunteers' experiences of delivering the support, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 40 publications
4
33
0
Order By: Relevance
“…The mothers participating in this study recounted that they were able to express their experiences according to their needs and by defying the idealised expectations that they face (Hays, ). It is noteworthy that the meaning of their common experience emerged through narration (see also Smith et al, ). However, they also indicated that solely sharing an experience of motherhood is not enough.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The mothers participating in this study recounted that they were able to express their experiences according to their needs and by defying the idealised expectations that they face (Hays, ). It is noteworthy that the meaning of their common experience emerged through narration (see also Smith et al, ). However, they also indicated that solely sharing an experience of motherhood is not enough.…”
Section: Discussionmentioning
confidence: 56%
“…Sharing an experience can bring about an understanding that peers cannot otherwise obtain (Borkman, , p. 198–199; Mead, Hilton, & Curtis, , p. 135; Munn‐Giddings & McVicar, , p. 29). Moreover, sharing an experience creates a basis for equal and reciprocal relationships between peers; because they are in the same situation, they are potentially both givers and receivers of support (Smith, Drennan, Mackenzie, & Greenwood, ).…”
Section: Introductionmentioning
confidence: 99%
“…Participants in this study reported the importance of being very clear and strict about the limits of the volunteer commitment and of communicating this to both volunteers and participants to avoid creating false expectations and dependencies. Not doing that can be emotionally draining for volunteers and negatively impact retention (47).…”
Section: Discussionmentioning
confidence: 99%
“…The voluntary sector is ideally placed to deliver low-cost and effective interventions and to increase access to disadvantaged populations (15,47). However, there have been few high quality trials evaluating community approaches that mobilise peer volunteers to promote active ageing (40).…”
Section: Discussionmentioning
confidence: 99%
“…Although the emerging need for volunteers to be involved in dementia care has been shown, few studies have addressed the significance of those who volunteer to be staff members in dementia cafés [35][36][37][38]. In Japan in particular, which is becoming a super-aged society, it is expected that support from not only health care professionals, but also local volunteers, will be expanded in dementia care, similar to the support by family caregivers for advanced activities such as hobbies [39].…”
Section: Discussionmentioning
confidence: 99%